The Concept of Integration of Science in Thought Prof. Imam Suprayogo - Ahmad Bachtiar Firdaus; Akhyak; Abdur Rosyid Hasan; Abdul Hakim Amrullah (Universitas Insan Budi Utomo, 2023)
Basically, the scientific sources of the Koran and al-hadith are the reference sources for all scientific fields. Science is not divided into religious knowledge and general science. This is the basis for researchers to raise the concept of integration of science in prof. suprayogo priest. This research is a qualitative descriptive study using the literature study method. The literature used is literature that is relevant to the discussion and research objectives, such as books, journal articles, proceedings and research reports. The result of this library research is that prof. Imam Suprayogo builds knowledge based on the integration of Islamic sciences and science which is a refinement or unification of sciences that have been considered separate. This thought is known as Tarbiyah Ulul Albab. The concept of integration of knowledge is taken in the metaphor of the tree of knowledge, namely a tree that is sturdy, has shady branches, has lush leaves, and bears heavy fruit because it is supported by strong roots.